2023
DOI: 10.1021/acs.iecr.3c00057
|View full text |Cite
|
Sign up to set email alerts
|

Polyacrylonitrile in the Preparation of Separation Membranes: A Review

Abstract: Polyacrylonitrile (PAN) is a hydrophilic polymer with good chemical resistance, low price, and excellent processability for fabricating membranes, especially for electrospun nanofiber-based membranes. In this review, the recent developments in the application and modification of PAN membranes are discussed, focusing on some applications such as pervaporation (PV), ion exchange, hemodialysis, membrane distillation, adsorption membrane, and water and wastewater treatment. First, the physicochemical characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 105 publications
(223 reference statements)
0
9
0
Order By: Relevance
“…Generally, air permeability and water vapor permeance in fabricsparameters largely governed by structural elements such as thickness, porosity, and fiber diameter , are essential factors influencing comfort and healing during bandage usage. As depicted in Figure a, the porosity of the prepared samples ranged from 91.2 to 80.1%, representing a slight change.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, air permeability and water vapor permeance in fabricsparameters largely governed by structural elements such as thickness, porosity, and fiber diameter , are essential factors influencing comfort and healing during bandage usage. As depicted in Figure a, the porosity of the prepared samples ranged from 91.2 to 80.1%, representing a slight change.…”
Section: Resultsmentioning
confidence: 99%
“…PAN, due to its excellent electrospinning and physical performance, is extensively studied to fabricate electrospun membranes used in textile, catalysis, energy, environmental engineering, and tissue engineering fields. In this work, a PAN electrospun membrane was prepared by solution electrospinning technology and used to fabricate electrospun composite NF. As shown in Figure a, the electrospun PAN fibers are straight and have an average diameter of 539 nm.…”
Section: Resultsmentioning
confidence: 99%
“…This makes it a suitable polymeric material for applications that work against amphiphilic molecules such as LPSs containing both oligosaccharides’ groups (hydrophilic moiety) connected to a lipid tail component. Furthermore, previous studies have shown that hydrophilic support membranes such as PAN promote wettability, are affordable, and provide good resistance to many solvents/chemicals Moreover, PAN is an environmentally friendly material whose source may come from a sustainable green process such as the recycling of waste PAN fibers, thus mitigating the accretion of polymeric material waste in the landfill . Furthermore, PS- b -P4VP was selected because of its self-assembly properties imparted by the incompatibility of its components, which results in a nanoporous structure.…”
Section: Resultsmentioning
confidence: 99%